2018
DOI: 10.2147/mder.s161889
|View full text |Cite
|
Sign up to set email alerts
|

Availability of right femoral vein as a route for tunneled hemodialysis catheterization

Abstract: PurposeThis study was performed to investigate the primary patency rate and catheter-related problems associated with use of the femoral vein as a route for tunneled hemodialysis catheterization compared with those of the right internal jugular vein as the first-choice route in patients undergoing maintenance hemodialysis.Patients and methodsTwenty-two patients underwent placement of indwelling tunneled hemodialysis catheters in the right internal jugular vein as the first option for maintenance hemodialysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In Shindo et al ( 10 )’s research, no factors, including age, sex, body mass index, dialysis condition, comorbidities and medications, were significantly associated with catheter survival. In another study, the previous history of femoral catheterisation was the only factor that affected the mean patency time ( 9 ).…”
Section: Discussionmentioning
confidence: 94%
“…In Shindo et al ( 10 )’s research, no factors, including age, sex, body mass index, dialysis condition, comorbidities and medications, were significantly associated with catheter survival. In another study, the previous history of femoral catheterisation was the only factor that affected the mean patency time ( 9 ).…”
Section: Discussionmentioning
confidence: 94%
“…1 TDC can be chosen as an alternative vascular access in case an arterio-venous fistula or arterio-venous graft failed or hard to create. 2 Furthermore, a TDC is apparently beneficial as a vascular access in cases with acute kidneys injuries, cases with end-stage chronic kidneys disorder that requires vascular access for temporary HD earlier to renal transplanting, and cases who should waited for the progress of an arterio-venous fistula or arteriovenous grafting, for HD maintenance thereafter a surgery. 3 A preceding report revealed that a TDC must be utilized in cases who are proposed to have an indwelling HD catheter for more than two weeks.…”
Section: Introductionmentioning
confidence: 99%